AQUATIC THERAPY AND BIO-PSYCHO-SOCIAL FEATURES OF THE FEMALE BODY AT THE AGE OF 25-35 YEARS - Sorin Raţă (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
Aquatic therapy is a beneficial therapy that is used for a variety of medical conditions. Aquatic therapy uses the physical properties of water to help the student to heal himself, to improve his biopsycho-motile potential and to socialize.